Increasing risk behaviour and high levels of undiagnosed HIV infection in a community sample of homosexual men. Issue 3 (28th May 2004) - Dodds, J P; Mercey, D E; Parry, J V; Johnson, A M
Abstract : Objectives: To estimate changes in sexual behaviour over time. To examine the proportion of undiagnosed HIV infection in a community sample of homosexual men. To explore the relation between HIV status, diagnosis, and sexual behaviour. Methods: Five cross sectional surveys of men attending selected gay community venues in London between 1996 and 2000 (n = 8052). Men were recruited in 45 to 58 social venues (including bars, clubs, and saunas) across London. Participants self completed an anonymous behavioural questionnaire. In 2000, participants in community venues provided anonymous saliva samples for testing for anti-HIV antibody. Results: The proportion of men having unprotected anal intercourse (UAI) increased significantly each year from 30% in 1996 to 42% in 2000 (p<<0.001). In 2000, 132 of 1206 (10.9%) saliva samples were HIV antibody positive. Of the HIV saliva antibody positive samples, 43/132 (32.5%) were undiagnosed. Around half of both diagnosed and undiagnosed HIV saliva positive men reported UAI in the past year. Of the 83% of men who reported their current perceived HIV status, 4.1% reported an incorrect status. HIV antibody positivity was associated with increasing numbers of UAI partners, and having a sexually transmitted infection (STI) in the past year (OR 2.15). Conclusions: Homosexual men continue to report increasing levels of UAI. HIV prevalence is high in this group, with many infections remaining undiagnosed. The high level of risky behaviour in HIV positive men, regardless of whether they are diagnosed, is of public health concern, in an era when HIV prevalence, antiretroviral resistance, and STI incidence are increasing.